Piezoelectric element and piezoelectric ceramic composition
By using a ceramic sintered body including the main phases of K, Na, Nb and Mn and the secondary phases of Mn and Nb at high temperatures, a ceramic structure with improved insulation performance is formed, which solves the problem of degradation of insulation performance in the prior art, and achieves both insulation and dielectric performance under high electric field conditions under high temperature environments.
Patent Information
- Application Number
- JP2024504536
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-12-08
- Filing Date
- 2023-06-26
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-06-26
AI Technical Summary
The prior art In the high electric field conditions under high temperature environments, the insulation performance of piezoelectric ceramics is degraded, making it difficult to maintain both insulation and dielectric properties.
A ceramic sintered body including the main phase of K, Na, Nb and Mn and the secondary phase of Mn and Nb is used to form a ceramic structure with improved insulation properties by sintering treatment in a reducing atmosphere at a high temperature.
It effectively suppresses the degradation of insulation performance under high electric field conditions under high temperature environments, while maintaining good dielectric performance.
Smart Images

Figure 0007666729000006 
Figure 0007666729000007 
Figure 0007666729000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a piezoelectric element. and Piezoelectric ceramic composition To things Regarding. [Background technology]
[0002] 2. Description of the Related Art Conventionally, piezoelectric ceramic electronic components such as ultrasonic sensors, piezoelectric buzzers, and piezoelectric actuators have been widely known as piezoelectric elements using piezoelectric materials.
[0003] Until now, lead zirconate titanate (PZT) compounds, which have the general formula Pb(Zr,Ti)O3, have been used as piezoelectric materials. In recent years, potassium sodium niobate (KNN) compounds, which have the general formula (K,Na)NbO3, have been attracting attention as lead-free piezoelectric materials.
[0004] Patent Document 1 discloses a piezoelectric ceramic consisting of a polycrystalline body having an alkali-containing niobate-based perovskite structure as a main phase, in which nickel and manganese are both present at the grain boundaries of the polycrystalline body, and in which, relative to 100 moles of the main phase, the manganese content is 0.1 moles or more and 2.0 moles or less, the nickel content is 0.1 moles or more and 2.0 moles or less, the lithium content is 0.2 moles or more and 3.0 moles or less, the silicon content is 0.2 moles or more and 3.0 moles or less, the strontium content is 2.0 moles or less, and the zirconium content is 2.0 moles or less. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6039715 Summary of the Invention [Problem to be solved by the invention]
[0006] According to Patent Document 1, by intentionally distributing a nickel-containing phase together with a manganese-containing phase at the grain boundaries of the main phase inside the piezoelectric ceramic, it is possible to improve the insulation performance while maintaining the piezoelectric characteristics of the piezoelectric element.
[0007] Patent Document 1 describes that in order to manufacture a piezoelectric element containing a piezoelectric ceramic, a mixed powder of raw material powders that form the main phase is pre-fired, and then MnO powder and NiO powder are mixed therein, that is, the pre-fired powder of the main phase, and the MnO powder and NiO powder are present as independent particles, and then the mixture is fired in an air atmosphere.
[0008] In the examples of Patent Document 1, the insulation performance is evaluated by the resistivity when a high DC electric field of 2 kV / mm is applied between the external electrodes of the piezoelectric element. However, in the piezoelectric ceramics described in Patent Document 1, when a high electric field exceeding 2 kV / mm is applied, the resistivity decreases in a high temperature environment compared to a room temperature environment, and it has been found that it is difficult to achieve both insulation performance and piezoelectric characteristics.
[0009] The present invention has been made to solve the above problems, and aims to provide a piezoelectric element in which degradation of insulating performance is suppressed when a high electric field is applied in a high-temperature environment. Another aim of the present invention is to provide a piezoelectric ceramic composition in which degradation of insulating performance is suppressed when a high electric field is applied in a high-temperature environment. Another aim of the present invention is to provide a method for manufacturing the piezoelectric element and a method for manufacturing the piezoelectric ceramic composition. [Means for solving the problem]
[0010] The piezoelectric element of the present invention includes a piezoelectric ceramic layer, and the piezoelectric ceramic layer is made of a ceramic sintered body in which a main phase containing K, Na, Nb and Mn and a secondary phase containing Mn and Nb are present.
[0011] The piezoelectric ceramic composition of the present invention is composed of a ceramic sintered body in which a main phase containing K, Na, Nb and Mn and a secondary phase containing Mn and Nb are present.
[0012] The method for producing a piezoelectric element of the present invention includes the steps of: mixing a K compound containing K, a Na compound containing Na, and a Nb compound containing Nb, and calcining the mixture to produce a calcined product; producing a ceramic green sheet including a Mn compound containing Mn and the calcined product; and firing the ceramic green sheet in a reducing atmosphere.
[0013] The method for producing a piezoelectric ceramic composition of the present invention includes the steps of mixing a K compound containing K, a Na compound containing Na, and a Nb compound containing Nb, and calcining the mixture to produce a calcined product, preparing a molded body containing a Mn compound containing Mn and the calcined product, and firing the molded body in a reducing atmosphere. Effect of the Invention
[0014] According to the present invention, it is possible to provide a piezoelectric element in which degradation of insulating performance is suppressed when a high electric field is applied in a high-temperature environment. Furthermore, according to the present invention, it is possible to provide a piezoelectric ceramic composition in which degradation of insulating performance is suppressed when a high electric field is applied in a high-temperature environment. Furthermore, according to the present invention, it is possible to provide a method for manufacturing the piezoelectric element and a method for manufacturing the piezoelectric ceramic composition. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a schematic example of a laminated piezoelectric element that is one embodiment of the piezoelectric element of the present invention. [Diagram 2] FIG. 2 is a perspective view that typically illustrates an example of a ceramic green sheet obtained in the process of producing a piezoelectric actuator. [Diagram 3] FIG. 3 is a perspective view that illustrates an example of a piezoelectric actuator on which external electrodes are formed. [Figure 4] FIG. 4 is a cross-sectional view that illustrates a schematic example of a single-plate type piezoelectric element, which is another embodiment of the piezoelectric element of the present invention. [Diagram 5]FIG. 5 is an example of a TEM image of a ceramic sintered body containing a primary phase and a secondary phase. [Figure 6] FIG. 6 is a mapping image of Mn element at the same location as FIG. [Figure 7] FIG. 7 is an example of an XRD pattern of a ceramic sintered body containing a primary phase and a secondary phase. [Figure 8] FIG. 8 shows an example of an XRD pattern of a ceramic sintered body obtained by adding Mn to a calcined product of a main phase containing a KNN-based compound and firing the calcined product in a reducing atmosphere in order to produce a single-plate type piezoelectric element. [Figure 9] FIG. 9 shows an example of an XRD pattern of a ceramic sintered body obtained by adding Mn to a calcined product of a main phase containing a KNN-based compound and firing the calcined product in a reducing atmosphere in order to produce a laminated piezoelectric element. [Figure 10] FIG. 10 shows an example of an XRD pattern of a ceramic sintered body obtained by adding Mn to a calcined product of a main phase containing a KNN-based compound and firing the calcined product in an air atmosphere in order to produce a single-plate type piezoelectric element. [Figure 11] FIG. 11 shows XRD patterns (2θ=33° or more and 35° or less) when the amount of Li added to a multi-layer piezoelectric element is changed. [Figure 12] FIG. 12 shows XRD patterns (2θ=41° or more and 45° or less) when the amount of Li added to a multi-layer piezoelectric element is changed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The piezoelectric element of the present invention will be described below. Note that the present invention is not limited to the following embodiments, and may be modified as appropriate within the scope of the present invention. In addition, a combination of multiple individual preferred configurations described in the following embodiments also constitutes the present invention.
[0017] The drawings shown below are schematic diagrams, and the dimensions, aspect ratio, and scale may differ from those of the actual product.
[0018] FIG. 1 is a cross-sectional view that illustrates a schematic example of a laminated piezoelectric element that is one embodiment of the piezoelectric element of the present invention.
[0019] 1 is an example of a laminated piezoelectric element. The piezoelectric actuator 10 includes piezoelectric ceramic layers 3 (3a-3h) and internal electrode layers 4 (4a-4g) provided on at least one main surface of the piezoelectric ceramic layers 3 and containing Ni as a main component (e.g., 30% by weight or more).
[0020] As shown in Fig. 1, the piezoelectric actuator 10 preferably further includes external electrodes 2 (2a, 2b) provided at both ends of a piezoelectric ceramic body 1 including alternating piezoelectric ceramic layers 3 and internal electrode layers 4. Although not shown in Fig. 1, external electrodes formed by a method such as sputtering may be provided on the front and back surfaces of the piezoelectric ceramic body 1. Examples of conductive materials constituting these external electrodes include NiCr, NiCu, Ag, Au, Pt, Ni, Cu, and Sn.
[0021] In the piezoelectric actuator 10, one ends of the internal electrode layers 4a, 4c, 4e, and 4g are electrically connected to one external electrode 2a, and one ends of the internal electrode layers 4b, 4d, and 4f are electrically connected to the other external electrode 2b. When a voltage is applied between the external electrodes 2a and 2b, the piezoelectric actuator 10 is displaced in any direction due to the piezoelectric effect. For example, the longitudinal piezoelectric effect causes displacement in the longitudinal direction (the lamination direction indicated by the arrow X), and the transverse piezoelectric effect causes displacement in the transverse direction (the direction perpendicular to the lamination direction).
[0022] The piezoelectric ceramic layer 3 is composed of a ceramic sintered body having a main phase containing K, Na, Nb, and Mn, and a secondary phase containing Mn and Nb. The ceramic sintered body constituting the piezoelectric ceramic layer 3 preferably further contains a secondary phase containing Mn and Ni. Details of each phase will be described later.
[0023] The piezoelectric actuator 10 is preferably manufactured by the following method. Such a method for manufacturing a piezoelectric element also constitutes one aspect of the present invention.
[0024] First, a K compound containing K, a Na compound containing Na, and a Nb compound containing Nb are prepared as ceramic raw materials. If necessary, a Li compound containing Li is prepared. The form of the compound of the ceramic raw material is not particularly limited, and examples include oxides, carbonates, hydrogen carbonates, and hydroxides. When adding a divalent element such as Ba, a tetravalent element such as Zr, or a rare earth element such as La, a compound of each element is prepared.
[0025] Next, a predetermined amount of the ceramic raw material is weighed out, and the weighed amount is put into a grinding machine such as a ball mill or a pot mill containing grinding media such as PSZ (partially stabilized zirconia) balls, and is thoroughly wet-ground in a solvent such as ethanol to obtain a mixture.
[0026] In addition, in the stage of preparing the mixture of ceramic raw materials, it is preferable not to add a Mn compound containing Mn.
[0027] The resulting mixture is dried and then calcined at a predetermined temperature (for example, 850° C. or higher and 1000° C. or lower) to synthesize a potassium sodium niobate (KNN)-based compound, and then crushed to obtain a calcined product.
[0028] A Mn compound such as MnCO3 is added to the calcined product. An organic binder and a dispersant are then added, and the mixture is wet mixed in a ball mill using pure water or an organic solvent (such as ethanol) as a solvent to obtain a ceramic slurry. The mixture is then molded using a doctor blade method or the like to produce ceramic green sheets.
[0029] Next, a conductive paste for internal electrode layers containing Ni as a main component is screen printed on the ceramic green sheets, thereby forming a conductive layer of a predetermined shape.
[0030] FIG. 2 is a perspective view that typically illustrates an example of a ceramic green sheet obtained in the process of producing a piezoelectric actuator.
[0031] 2, after the ceramic green sheets 5 (5a-5g) each having a conductive layer 6 (6a-6g) formed thereon are laminated, a ceramic green sheet 7a without a conductive layer 6 is laminated and pressure is applied to bond them together, thereby producing a ceramic laminate in which the ceramic green sheets 5 and the conductive layers 6 are alternately laminated.
[0032] The obtained ceramic laminate is cut to a predetermined size, placed in a firing jig such as an alumina scabbard, and subjected to a binder removal process at a predetermined temperature (e.g., 250°C or higher and 500°C or lower). Thereafter, it is fired in a reducing atmosphere at a predetermined temperature (e.g., 1000°C or higher and 1160°C or lower) to form a piezoelectric ceramic body 1 (ceramic sintered body) in which internal electrode layers 4 are embedded.
[0033] When the conductive layer 6 mainly composed of Ni and the ceramic green sheet 5 mainly composed of KNN-based compound are co-fired, it is necessary to fire them in a reducing atmosphere to prevent oxidation of Ni. Note that the oxygen partial pressure of the reducing atmosphere is preferably the equilibrium oxygen partial pressure at which Ni and NiO are in equilibrium or lower so that Ni is not oxidized.
[0034] Next, a conductive paste for external electrodes, composed of Ag or the like, is applied to the surface of the piezoelectric ceramic body to form external electrodes.
[0035] FIG. 3 is a perspective view that illustrates an example of a piezoelectric actuator on which external electrodes are formed.
[0036] 3, external electrodes 2a, 2b are formed by a method such as sputtering on both ends of the piezoelectric ceramic body 1. The external electrodes 2a, 2b need only have good adhesion to the piezoelectric ceramic body 1, and may be formed by a thin film formation method such as vacuum deposition, or may be formed by a method such as baking a conductive paste.
[0037] Thereafter, a predetermined polarization process is carried out to manufacture the piezoelectric actuator 10.
[0038] FIG. 4 is a cross-sectional view that illustrates a schematic example of a single-plate type piezoelectric element, which is another embodiment of the piezoelectric element of the present invention.
[0039] 4 is an example of a single-plate type piezoelectric element. The piezoelectric actuator 20 includes a piezoelectric ceramic layer 13.
[0040] 4, the piezoelectric actuator 20 includes external electrodes 12a and 12b provided on the front and back surfaces of a piezoelectric ceramic body 11 including a piezoelectric ceramic layer 13. Examples of conductive materials that form these external electrodes include NiCr, NiCu, Ag, Au, Pt, Ni, Cu, and Sn.
[0041] When a voltage is applied between the external electrodes 12a and 12b, the piezoelectric actuator 20 is displaced in any direction due to the piezoelectric effect. For example, the piezoelectric longitudinal effect causes displacement in the longitudinal direction (the direction indicated by the arrow Y), and the piezoelectric transverse effect causes displacement in the lateral direction (the direction perpendicular to the direction indicated by the arrow Y).
[0042] The piezoelectric ceramic layer 13 is composed of a ceramic sintered body having a main phase containing K, Na, Nb, and Mn, and a secondary phase containing Mn and Nb. The ceramic sintered body constituting the piezoelectric ceramic layer 13 may or may not further contain a secondary phase containing Mn and Ni. Details of each phase will be described later.
[0043] The piezoelectric actuator 20 can be produced, for example, by producing a molded body having a predetermined composition using a sheet method or press processing, applying a conductive paste for external electrodes containing Cu, Ni, Pt, or the like as a main component to both surfaces of the molded body, and co-firing the paste in a reducing atmosphere. The external electrodes may be formed by a method such as sputtering.
[0044] In the above embodiment, the laminated type and single plate type piezoelectric elements are exemplified, but the present invention is applicable to various types of piezoelectric elements.
[0045] In the piezoelectric element of the present invention, the piezoelectric ceramic layer is composed of a ceramic sintered body in which a main phase containing K, Na, Nb, and Mn and a secondary phase containing Mn and Nb (hereinafter also referred to as a first secondary phase) are present. Note that the piezoelectric ceramic composition composed of the ceramic sintered body described below also constitutes the present invention.
[0046] The main phase contains a KNN-based compound. The KNN-based compound has a perovskite structure and is represented by the general formula (K,Na)NbO3. The composition of the KNN-based compound is not particularly limited.
[0047] The main phase may contain elements other than K, Na, Nb, and Mn. For example, the main phase may contain Li as an alkali metal element. The main phase may also contain divalent elements such as Ba, Ca, and Sr, tetravalent elements such as Zr, Sn, and Hf, rare earth elements such as Sc, In, Yb, Y, Nd, Eu, Gd, Dy, Sm, Ho, Er, Tb, Lu, La, and Pr, Ta, Sb, Ni, etc.
[0048] The first secondary phase may include elements other than Mn and Nb.
[0049] The composition of the ceramic sintered body can be determined, for example, by observation and element distribution analysis using a transmission electron microscope (TEM) and energy dispersive X-ray analysis (EDX).
[0050] Fig. 5 is an example of a TEM image of a ceramic sintered body containing a primary phase and a secondary phase, and Fig. 6 is a mapping image of Mn element at the same location as Fig. 5.
[0051] In Fig. 6, the region where Mn element exists corresponds to the secondary phase. As shown in Figs. 5 and 6, the secondary phase is preferably scattered in the main phase.
[0052] The compositions of the main phase and the secondary phase contained in the ceramic sintered body shown in FIG.
[0053] [Table 1]
[0054] From Table 1, it can be seen that the main elements constituting the main phase are K, Na and Nb, whereas the main elements constituting the secondary phase are Mn and Nb.
[0055] Furthermore, by performing crystal structure analysis using X-ray diffraction (XRD), the crystal structure contained in the ceramic sintered body can be analyzed.
[0056] FIG. 7 is an example of an XRD pattern of a ceramic sintered body containing a primary phase and a secondary phase.
[0057] In Fig. 7, in addition to the peaks marked with ◆ due to the main phase containing KNN-based compounds and the peaks marked with ■ due to Ni, the peaks marked with ● due to the secondary phase containing Mn and Nb can be confirmed. In the example shown in Fig. 7, the secondary phase containing Mn and Nb has a Mn4Nb2O9 type crystal structure.
[0058] The above results suggest that Mn, which was added after synthesizing the main phase containing KNN-based compounds by calcination, extracts Nb from the B site during sintering. When Nb, which entered the crystal during calcination, leaves the crystal by being incorporated into a secondary phase (heterogeneous phase) containing Mn during sintering, Nb defects with acceptor function are generated in the B site of the main phase. This Nb defect contributes to charge compensation of 2.5 moles of oxygen defects per mole, which is thought to lead to improved insulation performance in high-temperature environments. Note that a portion of the Nb in the B site may be replaced by elements such as Zr, in which case the elements such as Zr may be incorporated into a secondary phase (heterogeneous phase) containing Mn and leave the crystal.
[0059] In addition, K and Na (or Li) that are dissolved in the A site of the main phase crystal may be incorporated into a secondary phase (heterogeneous phase) containing Mn and exit the crystal, forming K defects and Na defects (or Li defects) in the A site. These defects also provide acceptor function, so they all contribute to charge compensation of oxygen defects, which is thought to lead to improved insulation performance in high-temperature environments.
[0060] Thus, in the present invention, it is believed that the elements contained in the main phase are contained in the secondary phase, thereby forming defects in the main phase and improving the insulating performance in high temperature environments.
[0061] FIG. 8 shows an example of an XRD pattern of a ceramic sintered body obtained by adding Mn to a calcined product of a main phase containing a KNN-based compound and firing the calcined product in a reducing atmosphere in order to produce a single-plate type piezoelectric element.
[0062] As shown in Fig. 8, the secondary phase containing Mn and Nb preferably has a peak in the range of 2θ = 33° to 35° in crystal structure analysis using X-ray diffraction. In the example shown in Fig. 8, the secondary phase containing Mn and Nb has a Mn4Nb2O9 type crystal structure.
[0063] In a crystal structure analysis using X-ray diffraction, when the maximum peak intensity of the main phase is I0 and the maximum peak intensity of the secondary phase containing Mn and Nb in the range of 2θ=33° or more and 35° or less is I1, the maximum peak intensity ratio represented by I1 / I0 is preferably more than 0.019 and less than 0.070.
[0064] FIG. 9 shows an example of an XRD pattern of a ceramic sintered body obtained by adding Mn to a calcined product of a main phase containing a KNN-based compound and firing the calcined product in a reducing atmosphere in order to produce a laminated piezoelectric element.
[0065] In the laminated piezoelectric element, an internal electrode layer containing Ni as a main component is provided on at least one of the main surfaces of the piezoelectric ceramic layer. In this case, as shown in Fig. 9, the secondary phase containing Mn and Nb preferably has a peak in the range of 2θ=33° to 35° in the crystal structure analysis using X-ray diffraction. In the example shown in Fig. 9, the secondary phase containing Mn and Nb has a ZnNb2Mn3O9 type crystal structure.
[0066] When an internal electrode layer containing Ni as a main component is provided on at least one main surface of the piezoelectric ceramic layer, it is preferable that the ceramic sintered body further contains a secondary phase containing Mn and Ni (hereinafter also referred to as a second secondary phase).
[0067] The second secondary phase may include elements other than Mn and Ni.
[0068] As shown in Fig. 9, the secondary phase containing Mn and Ni preferably has a peak in the range of 2θ = 41° or more and 44° or less in crystal structure analysis using X-ray diffraction. In the example shown in Fig. 9, the secondary phase containing Mn and Ni is Mn 0.5 Ni 0.5 O (i.e. MnNiO2) type crystal structure.
[0069] In a crystal structure analysis using X-ray diffraction, when the maximum peak intensity of the main phase is I0 and the maximum peak intensity of the secondary phase containing Mn and Ni in the range of 2θ=41° or more and 44° or less is I2, the maximum peak intensity ratio represented by I2 / I0 is preferably greater than 0 and less than 0.04.
[0070] As shown in FIGS. 8 and 9, it is preferable that the ceramic sintered body does not have a peak near 2θ=29° in crystal structure analysis using X-ray diffraction.
[0071] FIG. 10 shows an example of an XRD pattern of a ceramic sintered body obtained by adding Mn to a calcined product of a main phase containing a KNN-based compound and firing the calcined product in an air atmosphere in order to produce a single-plate type piezoelectric element.
[0072] In the example shown in Figure 10, which was fired in an air atmosphere, unlike the example shown in Figure 8, which was fired in a reducing atmosphere, it can be confirmed that no secondary phase with a peak in the range of 2θ = 33° to 35° is formed in the crystal structure analysis using X-ray diffraction. Instead, peaks of LiMn2O4 and ZrO2 can be confirmed. Note that the peak near 2θ = 34° is a ZrO2 peak, which is different from the peak of the secondary phase containing Mn and Nb.
[0073] FIG. 11 shows XRD patterns (2θ=33° or more and 35° or less) when the amount of Li added to a multi-layer piezoelectric element is changed.
[0074] As shown in FIG. 11, in the range of 2θ=33° or more and 35° or less, peaks having Mn4Nb2O9 type or ZnNb2Mn3O9 type crystal structures as secondary phases containing Mn and Nb can be confirmed.
[0075] FIG. 12 shows XRD patterns (2θ=41° or more and 45° or less) when the amount of Li added to a multi-layer piezoelectric element is changed.
[0076] As shown in FIG. 12, in the range of 2θ=41° or more and 44° or less, a peak having an MnNiO2 type crystal structure as a secondary phase containing Mn and Ni can be confirmed.
[0077] The present specification discloses the following:
[0078] <1> A piezoelectric ceramic layer is provided. The piezoelectric ceramic layer is a piezoelectric element composed of a ceramic sintered body having a main phase containing K, Na, Nb and Mn and a secondary phase containing Mn and Nb.
[0079] <2> The secondary phase containing Mn and Nb has a peak in the range of 2θ=33° to 35° in crystal structure analysis using X-ray diffraction. <1> The piezoelectric element according to claim 1 .
[0080] <3> In the crystal structure analysis using the X-ray diffraction, when the maximum peak intensity of the main phase is I0 and the maximum peak intensity of the secondary phase containing Mn and Nb in the range of 2θ = 33 ° or more and 35 ° or less is I1, the maximum peak intensity ratio represented by I1 / I0 is more than 0.019 and less than 0.070, <2> The piezoelectric element according to claim 1 .
[0081] <4> Further comprising an internal electrode layer provided on at least one main surface of the piezoelectric ceramic layer and containing Ni as a main component. <1> ~ <3> 13. A piezoelectric element according to any one of claims 1 to 12.
[0082] <5> The ceramic sintered body further comprises a secondary phase containing Mn and Ni. <4> The piezoelectric element according to claim 1 .
[0083] <6> The secondary phase containing Mn and Ni has a peak in the range of 2θ=41° to 44° in crystal structure analysis using X-ray diffraction. <5> The piezoelectric element according to claim 1 .
[0084] <7> In the crystal structure analysis using the X-ray diffraction, when the maximum peak intensity of the main phase is I0 and the maximum peak intensity of the secondary phase containing Mn and Ni in the range of 2θ = 41 ° or more and 44 ° or less is I2, the maximum peak intensity ratio represented by I2 / I0 is greater than 0 and less than 0.04. <6> The piezoelectric element according to claim 1 .
[0085] <8> A piezoelectric ceramic composition comprising a ceramic sintered body having a main phase containing K, Na, Nb and Mn, and a secondary phase containing Mn and Nb.
[0086] <9> The secondary phase containing Mn and Nb has a peak in the range of 2θ=33° to 35° in crystal structure analysis using X-ray diffraction. <8> The piezoelectric ceramic composition according to claim 1.
[0087] <10> In the crystal structure analysis using the X-ray diffraction, when the maximum peak intensity of the main phase is I0 and the maximum peak intensity of the secondary phase containing Mn and Nb in the range of 2θ = 33 ° or more and 35 ° or less is I1, the maximum peak intensity ratio represented by I1 / I0 is more than 0.019 and less than 0.070, <9> The piezoelectric ceramic composition according to claim 1.
[0088] <11> The ceramic sintered body further comprises a secondary phase containing Mn and Ni. <8> ~ <10> 13. The piezoelectric ceramic composition according to claim 12,
[0089] <12> The secondary phase containing Mn and Ni has a peak in the range of 2θ=41° to 44° in crystal structure analysis using X-ray diffraction. <11> The piezoelectric ceramic composition according to claim 1.
[0090] <13> In the crystal structure analysis using the X-ray diffraction, when the maximum peak intensity of the main phase is I0 and the maximum peak intensity of the secondary phase containing Mn and Ni in the range of 2θ = 41 ° or more and 44 ° or less is I2, the maximum peak intensity ratio represented by I2 / I0 is less than 0.04. <12> The piezoelectric ceramic composition according to claim 1.
[0091] <14> A step of mixing a K compound containing K, a Na compound containing Na, and a Nb compound containing Nb, and calcining the mixture to prepare a calcined product; preparing a ceramic green sheet including a Mn-containing Mn compound and the calcined product; and firing the ceramic green sheet in a reducing atmosphere.
[0092] <15> The method further includes a step of forming a conductive layer on the ceramic green sheet using a conductive paste containing Ni as a main component before the step of firing the ceramic green sheet. <14> A method for manufacturing the piezoelectric element according to claim 1.
[0093] <16> The method further includes a step of stacking the ceramic green sheets on which the conductive layer is formed to produce a ceramic laminate before the step of firing the ceramic green sheets. <15> A method for manufacturing the piezoelectric element according to claim 1.
[0094] <17> A step of mixing a K compound containing K, a Na compound containing Na, and a Nb compound containing Nb, and calcining the mixture to prepare a calcined product; preparing a molded body containing a Mn compound and the calcined product; and firing the compact in a reducing atmosphere. EXAMPLES
[0095] EXAMPLES Hereinafter, examples that more specifically disclose the piezoelectric element of the present invention will be described, however, the present invention is not limited to these examples.
[0096] [Example 1-1] In Example 1-1, laminated piezoelectric elements having different amounts of Mn added as shown in Table 2 were fabricated.
[0097] First, K2CO3, Na2CO3, Li2CO3, Nb2O3, and BaZrO3 were prepared as ceramic raw materials. After weighing out a predetermined amount of the ceramic raw materials, the weighed materials were put into a ball mill and thoroughly wet-pulverized to obtain a mixture. After drying the obtained mixture, it was calcined and crushed to obtain a calcined product.
[0098] Next, the calcined product and MnCO3 were prepared, weighed out in a predetermined amount, and put into a ball mill together with an organic binder, a dispersant, and a solvent (pure water or an organic solvent (ethanol, etc.)) and thoroughly wet mixed. After that, the mixture was molded using a doctor blade method to obtain a ceramic green sheet.
[0099] Next, a conductive paste for an internal electrode layer containing Ni as a main component was used to form a conductive layer having a predetermined pattern on the ceramic green sheet by a screen printing method. After stacking a predetermined number of ceramic green sheets with the conductive layer formed thereon, ceramic green sheets without the conductive layer formed thereon were stacked and pressure-bonded. Thus, a ceramic laminate was produced.
[0100] A piezoelectric ceramic body (ceramic sintered body) including an internal electrode layer whose main component is Ni was produced by firing the ceramic laminate in a reducing atmosphere adjusted to be 0.5 orders of magnitude more reducing than the equilibrium oxygen partial pressure at which Ni and NiO are in equilibrium.
[0101] Both main surfaces of the obtained piezoelectric ceramic body were subjected to a sputtering process to form external electrodes made of Ag. Then, an electric field of 3 kV / mm was applied for 3 minutes in air at room temperature to perform a polarization process. In this manner, samples 1 to 7 were produced.
[0102] [Example 1-2] In Example 1-2, laminated piezoelectric elements were produced with different amounts of Mn added, as shown in Table 3. The piezoelectric elements were produced in the same manner as in Example 1-1, except that the ceramic laminate was fired in a reducing atmosphere adjusted to be one order of magnitude less than the equilibrium oxygen partial pressure. As a result, samples 8 to 14 were produced.
[0103] [Example 2-1] In Example 2-1, the amount of Mn added was fixed at 5 mol%, and stacked piezoelectric elements with different amounts of NiO added were prepared as shown in Table 4. As in Example 1-1, the ceramic stack was fired in a reducing atmosphere adjusted to be 0.5 orders of magnitude less reducing than the equilibrium oxygen partial pressure, to prepare piezoelectric elements. Samples 15 to 22 were prepared in this manner.
[0104] [Example 2-2] In Example 2-2, the amount of Mn added was fixed at 5 mol%, and stacked piezoelectric elements with different amounts of NiO added were prepared as shown in Table 5. The piezoelectric elements were prepared in the same manner as in Example 2-1, except that the ceramic stack was fired in a reducing atmosphere adjusted to be one order of magnitude less than the equilibrium oxygen partial pressure. As a result, samples Nos. 23 to 30 were prepared.
[0105] For each of the samples Nos. 1 to 30, a crystal structure analysis was carried out using X-ray diffraction to analyze the crystal structure contained in the ceramic sintered body.
[0106] As a result, it was confirmed that a main phase containing a KNN-based compound was present in the ceramic sintered body in Samples 1 and 8, which did not contain Mn, while it was confirmed that a main phase containing a KNN-based compound, a secondary phase containing Mn and Nb, and a secondary phase containing Mn and Ni were present in the ceramic sintered body in Samples 2 to 7 and 9 to 30, which contained Mn.
[0107] In the crystal structure analysis using X-ray diffraction of each of the samples of sample numbers 1 to 30, the maximum peak intensity of the main phase is I0, the maximum peak intensity of the secondary phase containing Mn and Nb in the range of 2θ=33° to 35° is I1, and the maximum peak intensity of the secondary phase containing Mn and Ni in the range of 2θ=41° to 44° is I2. The maximum peak intensity ratios represented by I1 / I0 and I2 / I0 are shown in Tables 2 to 5. As described above, in samples 1 and 8, the peaks of the secondary phase containing Mn and Nb and the peaks of the secondary phase containing Mn and Ni could not be detected, so the maximum peak intensity ratios are indicated by "-".
[0108] The insulating performance of each of the samples Nos. 1 to 30 was evaluated by measuring the resistivity ρ (Ω m) when a DC electric field of 3 kV / mm was applied at room temperature (25°C), 85°C, or 125°C. The log ρ values of each sample are shown in Tables 2 to 5.
[0109] For each sample numbered 1 to 30, the piezoelectric constant d 31The piezoelectric properties were evaluated by measuring the piezoelectric constant d 31 is the relative dielectric constant ε measured by an impedance analyzer 33 and the electromechanical coupling coefficient k 31 The piezoelectric constant d of each sample was calculated. 31 The values are shown in Tables 2 to 5.
[0110] [Table 2]
[0111] [Table 3]
[0112] [Table 4]
[0113] [Table 5]
[0114] In Tables 2 to 5, samples marked with * are comparative examples outside the scope of the present invention.
[0115] From the results of Tables 2 to 5, it is considered that a secondary phase containing Mn and Nb is formed in a ceramic sintered body by adding Mn to a sintered product of a main phase containing a KNN compound and sintering the product in a reducing atmosphere. Furthermore, it is considered that a secondary phase containing Mn and Ni is also formed in the ceramic sintered body by co-sintering with a conductive layer (internal electrode layer) mainly composed of Ni.
[0116] From Table 2, in samples 4 to 6, in which the maximum peak intensity ratio represented by I1 / I0 exceeds 0.019 and is less than 0.070, the resistivity logρ at 85°C is greater than 8.5 and the resistivity logρ at 125°C is greater than 7, and thus the samples have sufficient insulating performance. In addition, in samples 2 to 6, in which the maximum peak intensity ratio represented by I2 / I0 exceeds 0 and is less than 0.04, the piezoelectric constant d31 The piezoelectric coefficient is larger than 40 pC / N, and the piezoelectric properties are excellent. [Explanation of symbols]
[0117] 1, 11 Piezoelectric ceramic body 2, 2a, 2b, 12a, 12b external electrode 3, 3a-3h, 13 Piezoelectric ceramic layer 4, 4a~4g internal electrode layer 5, 5a~5g, 7a Ceramic green sheet 6, 6a~6g conductive layer 10, 20 Piezoelectric actuator (piezoelectric element)
Claims
1. A piezoelectric ceramic layer is provided. The piezoelectric ceramic layer is composed of a ceramic sintered body having a main phase containing K, Na, Nb and Mn and a secondary phase containing Mn and Nb.
2. 2. The piezoelectric element according to claim 1, wherein the secondary phase containing Mn and Nb has a peak in the range of 2θ=33° or more and 35° or less in crystal structure analysis using X-ray diffraction.
3. In the crystal structure analysis using the X-ray diffraction, the maximum peak intensity of the main phase is I 0 The maximum peak intensity of the secondary phase containing Mn and Nb in the range of 2θ = 33 ° or more and 35 ° or less is I 1 Then, I 1 / I 0 The piezoelectric element according to claim 2 , wherein the maximum peak intensity ratio represented by the formula (I) is greater than 0.019 and less than 0.
070.
4. 4. The piezoelectric element according to claim 1, further comprising an internal electrode layer provided on at least one main surface of the piezoelectric ceramic layer and containing Ni as a main component.
5. The piezoelectric element according to claim 4 , wherein the ceramic sintered body further contains a secondary phase containing Mn and Ni.
6. 6. The piezoelectric element according to claim 5, wherein the secondary phase containing Mn and Ni has a peak in a range of 2θ=41° or more and 44° or less in crystal structure analysis using X-ray diffraction.
7. In the crystal structure analysis using the X-ray diffraction, the maximum peak intensity of the main phase is I 0 The maximum peak intensity of the secondary phase containing Mn and Ni in the range of 2θ = 41 ° or more and 44 ° or less is I 2 Then, I 2 / I 0 The piezoelectric element according to claim 6 , wherein the maximum peak intensity ratio represented by the formula (I) is greater than 0 and less than 0.
04.
8. A piezoelectric ceramic composition comprising a ceramic sintered body having a main phase containing K, Na, Nb and Mn and a secondary phase containing Mn and Nb.
9. 9. The piezoelectric ceramic composition according to claim 8, wherein the secondary phase containing Mn and Nb has a peak in the range of 2θ=33° or more and 35° or less in crystal structure analysis using X-ray diffraction.
10. In the crystal structure analysis using the X-ray diffraction, the maximum peak intensity of the main phase is I 0 The maximum peak intensity of the secondary phase containing Mn and Nb in the range of 2θ = 33 ° or more and 35 ° or less is I 1 Then, I 1 / I 0 The piezoelectric ceramic composition according to claim 9, wherein the maximum peak intensity ratio represented by the formula (I) is greater than 0.019 and less than 0.
070.
11. The piezoelectric ceramic composition according to any one of claims 8 to 10, wherein the ceramic sintered body further contains a secondary phase containing Mn and Ni.
12. 12. The piezoelectric ceramic composition according to claim 11, wherein the secondary phase containing Mn and Ni has a peak in the range of 2θ=41° or more and 44° or less in crystal structure analysis using X-ray diffraction.
13. In the crystal structure analysis using the X-ray diffraction, the maximum peak intensity of the main phase is I 0 The maximum peak intensity of the secondary phase containing Mn and Ni in the range of 2θ = 41 ° or more and 44 ° or less is I 2 Then, I 2 / I 0 The piezoelectric ceramic composition according to claim 12, wherein the maximum peak intensity ratio represented by the formula (I) is less than 0.04.
Citation Information
Patent Citations
Interlocking switch for electric product
JP1985039715A
Structure of pad electrode
JP1989089333A
Leadless piezoelectric ceramic composition, piezoelectric element prepared using the same, and method of producing leadless piezoelectric ceramic composition
JP2015202972A
Piezoelectric film, piezoelectric laminate, piezoelectric element, and manufacturing method of piezoelectric laminate
JP2021141187A
Piezoelectric element, and manufacturing method of piezoelectric element
JP2023066639A